1995
DOI: 10.2307/3283947
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi in Wild Raccoons, Opossums, and Triatomine Bugs in Southeast Georgia, U.S.A.

Abstract: The prevalence of Trypanosoma cruzi infection among wild opossums and raccoons live-trapped in 6 southeast Georgia counties was determined. Epimastigotes typical of T. cruzi were observed in liver infusion tryptose medium cultures of blood from 6 of 39 opossums (15.4%) and 12 of 54 raccoons (22.2%). Trypomastigotes (6,000/ml) were observed in a wet mount of blood from 1 of the animals, a raccoon trapped on St. Catherines Island in Liberty County. In addition, T. cruzi parasites were observed in the gut content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…It is evident that T. cruzi has always been present in Mexico as well as in the United States (Barr et al 1991, Hagar & Rahimtoola 1991, Pung et al 1995, Herwaldt et al 2000, Barnabe et al 2001, the geographic distribution of T. cruzi ranges from the United States to Southern Argentina. According to the information we have compiled about a variety of different topics related to Chagas disease in Mexico, it is clear that we must develop better approaches to understand all of the relevant variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that T. cruzi has always been present in Mexico as well as in the United States (Barr et al 1991, Hagar & Rahimtoola 1991, Pung et al 1995, Herwaldt et al 2000, Barnabe et al 2001, the geographic distribution of T. cruzi ranges from the United States to Southern Argentina. According to the information we have compiled about a variety of different topics related to Chagas disease in Mexico, it is clear that we must develop better approaches to understand all of the relevant variables.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoculture studies have demonstrated that 17 (14%) of 126 opossums from east-central Alabama (Olsen et al, 1964), 88 (16%) of 552 opossums from southwestern Georgia and northwestern Florida (McKeever et al, 1958), 16 (33%) of 48 opossums from Louisiana (Barr et al, 1992), 6 (15%) of 39 opossums from southeast Georgia (Pung et al, 1995), and 1 (8%) of 12 opossums from North Carolina (Karsten et al, 1992) were infected with T. cruzi. Brown et al (2010) used an IFAT and reported that antibodies were present in 14 (52%) of 27 opossums from Florida, 118 (28%) of opossums from Georgia, and .…”
Section: Discussionmentioning
confidence: 99%
“…All but 1 of the previous studies on the prevalence of T. cruzi in North American opossums has been conducted by hemoculture (McKeever et al, 1958;Olsen et al, 1964;Barr et al, 1991;Karsten et al, 1992;Pung et al, 1995;Brown et al, 2010). Hemoculture studies have demonstrated that 17 (14%) of 126 opossums from east-central Alabama (Olsen et al, 1964), 88 (16%) of 552 opossums from southwestern Georgia and northwestern Florida (McKeever et al, 1958), 16 (33%) of 48 opossums from Louisiana (Barr et al, 1992), 6 (15%) of 39 opossums from southeast Georgia (Pung et al, 1995), and 1 (8%) of 12 opossums from North Carolina (Karsten et al, 1992) were infected with T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the US T. cruzi has been found in 11.4% of opossums and 22% of raccoons, together with infected triatomine bugs in the state of Georgia (Pung et al 1995). In certain areas of that state, up to 43% of the raccoons were infected (Pietrzak & Pung 1998).…”
Section: The Ecobiology Of T Cruzimentioning
confidence: 99%